2020
DOI: 10.5539/ies.v14n1p115
|View full text |Cite
|
Sign up to set email alerts
|

The Association Between Parent Participation in School Management and Student Achievement in Eight Countries and Economies

Abstract: Parent participation in school management has been promoted as a strategy for holding schools accountable for education quality and outcomes. However, the evidence has proven inconclusive and limited in explaining mechanisms to affect student achievement. By using public school student data derived from the Programme for International Student Assessment 2015, this study examines how 1) participation of a student’s own parents in school management, which would affect their learning support at home and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 30 publications
0
2
0
1
Order By: Relevance
“…Uno de estos derechos se relaciona con la participación en los centros, de manera individual, asistiendo a las reuniones, formando parte de las actividades organizadas por el centro, o bien de manera colectiva mediante las asociaciones de padres y madres y el consejo escolar (Appiah-Kubi y Amoako, 2020; Bernard y Llevot, 2015;Gokalp et al, 2021). Esto pone también de manifiesto que lo que importa no es tanto la participación como el compromiso (Sakamoto, 2021). Este derecho a participar muchas veces queda difuminado, bien por el Revista Española de Discapacidad, 11(1), 139-162 desconocimiento de los mismos de la labor que pueden desarrollar en los centros, por el desinterés de estos en llevar a cabo tareas extra o por la carencia de una conciliación familiar efectiva que les permita participar (Belmonte et al, 2020).…”
Section: La Necesidad De Construir Comunidades Escolares Inclusivasunclassified
“…Uno de estos derechos se relaciona con la participación en los centros, de manera individual, asistiendo a las reuniones, formando parte de las actividades organizadas por el centro, o bien de manera colectiva mediante las asociaciones de padres y madres y el consejo escolar (Appiah-Kubi y Amoako, 2020; Bernard y Llevot, 2015;Gokalp et al, 2021). Esto pone también de manifiesto que lo que importa no es tanto la participación como el compromiso (Sakamoto, 2021). Este derecho a participar muchas veces queda difuminado, bien por el Revista Española de Discapacidad, 11(1), 139-162 desconocimiento de los mismos de la labor que pueden desarrollar en los centros, por el desinterés de estos en llevar a cabo tareas extra o por la carencia de una conciliación familiar efectiva que les permita participar (Belmonte et al, 2020).…”
Section: La Necesidad De Construir Comunidades Escolares Inclusivasunclassified
“…As such, primary education pupils boost their spirits and encourage them to do well in class if they see their parents participate in school's activities and programs whether online or face to face interaction. Meanwhile, Sakamoto (2020) found that parents have already provided an optimal level of learning support even before they participated in school management. Shared Leadership.…”
Section: Parental Involvementmentioning
confidence: 99%
“…Este factor se relaciona con la facilidad con la que el personal administrativo de los planteles educativos (Sakamoto, 2020), brinda efectivamente sus servicios o solicitudes, e identifica las formas en que la gobernanza educacional (Sakız et al, 2021), pues, demuestra el enfoque en la resolución de este conflicto. La comunicación del personal con los representantes de los estudiantes es un factor clave para resolver las quejas (Skapinaki & Salamoura, 2020).…”
Section: Aspecto No Académicounclassified